Has the Covid-19 pandemic affected the practice of Orthopedics and Traumatology? - Anıl Gülcü; Aziz Atik; Ahmet Aksoy; Serdar Sargın (Acta Medica Alanya)
About the impact of the Covid-19 pandemic on the practice of Orthopedics and Traumatology